2020
DOI: 10.4158/accr-2019-0585
|View full text |Cite
|
Sign up to set email alerts
|

A Common Pituitary Autoantibody in Two Patients with Immune Checkpoint Inhibitor-Mediated Hypophysitis: ZCCHC8

Abstract: Objective: Hypophysitis is an increasingly recognized adverse effect of immune checkpoint inhibitor (ICI) therapy for malignancy. However, the mechanisms through which ICIs induce hypophysitis are largely unknown. We aim to describe 2 cases of ICI-mediated hypophysitis and perform autoantibody profiling on serial samples from these patients to determine if common autoantibodies could be identified. Methods: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In our patient, three pituitary axes were affected: the adrenocorticotropic, thyroid and gonadotrophic axes. This is a rather rare presentation reported in three other patients in the currently available literature [20][21][22]27]. The time to onset was relatively short and ranged from three to nine months and two of the patients were diagnosed with melanoma [14].…”
Section: Hormonal Disturbancesmentioning
confidence: 88%
See 2 more Smart Citations
“…In our patient, three pituitary axes were affected: the adrenocorticotropic, thyroid and gonadotrophic axes. This is a rather rare presentation reported in three other patients in the currently available literature [20][21][22]27]. The time to onset was relatively short and ranged from three to nine months and two of the patients were diagnosed with melanoma [14].…”
Section: Hormonal Disturbancesmentioning
confidence: 88%
“…Defects of the neurohypophysis are mainly reported in the context of pituitary metastasis [4]. Ascertainment of secondary adrenal failure used different testing strategies, including morning cortisol and ACTH [9,[11][12]15,[17][18][19][20][21][22][23][24][25][26][27], short Synacthen test [12,[16][17][18]21] and corticotropin-releasing hormone (CRH) stimulation test [12,16,24]. In our patient, three pituitary axes were affected: the adrenocorticotropic, thyroid and gonadotrophic axes.…”
Section: Hormonal Disturbancesmentioning
confidence: 98%
See 1 more Smart Citation
“…The correlation analysis showed that the ZCCHC gene family was associated with immune function in THCA, which was consistent with the results of previous studies, showing that ZCCHCs were associated with immunity. For example, ZCCHC17 is identified as a novel marker for the diagnosis and prognostic assessment of hepatocellular carcinoma (HCC) by regulating the immune cells in the tumor microenvironment (TME) of HCC patients, with specific reference value for immunotherapy of HCC, suggesting that ZCCHCs are associated with immunity [ 32 , 40 ]. Both GO and PPI network analyses suggested that the ZCCHC gene family probably functioned by regulating other proteins through metabolic pathways such as zinc ion binding and transition metal ion binding.…”
Section: Discussionmentioning
confidence: 99%
“…The development of autoantibodies has been described in a number of IRAEs, including diabetes and hypophysitis ( 31 , 32 , 33 ). Two studies have now reported the development of auto-antibodies in hypophysitis ( 34 , 35 ), although notably there was no common antibodies described, and both studies included patients with both ipilimumab hypophysitis and the more limited ACTH deficiency with nivolumab or pembrolizumab. A further study suggested that hypophysitis was more common in certain HLA types, most notably DR15 ( 36 ), although again the hypophysitis cohort was heterogeneous.…”
Section: Pituitarymentioning
confidence: 99%